Into the field : a foreign correspondent's notebook - Dahlby, Tracy (University of Texas Press, 2014)
"In this lively memoir of covering the Asian Pacific Rim, a veteran reporter for National Geographic and Newsweek tells "the stories behind the stories" that reveal the hard work, skill, and luck it takes to be a successful foreign correspondent. His real-world advice about everything from successful travel planning, to finding a great local fixer, to dealing with circumstances that can range from friendly to formidable makes this book a practical how-to guide for aspiring journalists"--